MARIALITIC SCAPOLITE OCCURENCES FROM THE KIMMERIA-LEFKOPETRA METAMORPHIC CONTACT, XANTHI (N. GREECE) - Mouchos, E.; Papadopoulou, L.; Williamson, B.J.; Christofides, G. (Bulletin of the Geological Society of Greece, 2016)
Emplacement of the Xanthi Plutonic Complex within the Rhodope Massif of N. Greece created an extensive metamorphic aureole around the plutonite. The aureole contains two areas of intense scapolitization in the contacts between granodiorite and biotitegneiss and between monzonite and sandstone, the latter cross-cut by andesite dykes. This paper reports the results of a mineralogical and geochemical study into the formation of the scapolites and particularly the nature of the plutonite-derived hydrothermal fluids from which scapolites were formed.